Consensus for Mixed-Order Multiagent Systems over Jointly Connected Topologies via Impulse Control - Fenglan Sun; Xiaogang Liao; Yongfu Li; Feng Liu (Complexity)
Because of the complexity of the environment, the dynamics of agents in the same system may be different. That is, the dynamics of some agents may be first ordered, and the others may be second ordered, even high ordered. In addition, the network topologies of systems are always varying over time. Because of these facts, this paper studies the consensus problem of the mixed-order multiagent networks over the jointly connected topologies. By adopting the impulse control technique, some control protocols are proposed based on the information of the agents themselves and their neighbors. Several simulation results are given to verify the correctness of the theoretical results.